Interaction of Arsenic with Zinc and Organics in a Rice (Oryza sativa L.)–Cultivated Field in India - Dilip Kumar Das; T. K. Garai; S. Sarkar; Pintu Sur (The Scientific World Journal)
A laboratory experiment on an Inceptisol with pH 7.6, organic carbon 6.8 g kg–1, and 0.5 M NaHCO3 extractable arsenic 0.4 mg kg–1 was conducted to study the interaction effect of graded levels of arsenic (0, 5, and 10 mg kg–1) with zinc (0, 10, and 20 mg kg–1) and organics (0, 1, and 2% on soil weight basis) separately on the mobilization of arsenic in soils.The results show that the amount of 0.5 M NaHCO3 extractable arsenic at pH 8.5 increased with the progress of submergence up to 35 days. However, the increase in arsenic concentration was correlated with decreasing application of graded levels of Zn as zinc sulfate. The intensity of reduction varied with varying levels of Zn, being higher (0.73–2.72 mg kg–1) in the treatment where Zn was at 10 mg kg–1 and lower (0.70–1.08 mg kg–1) with Zn at 20 mg kg–1 application.The amount of arsenic content in the soil significantly decreased with the application of varying levels of organics. However, such depressive effect was found more pronounced with well-decomposed farm yard manure than that of vermicompost. The results of field experiments showed that the grain yield between continuous flooding (4.84 t ha–1) and intermittent flooding up to 40 days after transplanting then continuous flooding (4.83 t ha–1) with the application of ZnSO4 at 25 kg ha–1 did not vary. The lowest grain yield (3.65 t ha–1) was recorded in the treatment where intermittent flooding was maintained throughout the growth period without the application of Zn. The amount of arsenic content was, however, recorded much lower in the treatment where intermittent flooding throughout the growth period was maintained with ZnSO4.